High heritability of telomere length and low heritability of telomere shortening in wild birds. Issue 23 (10th October 2021) - Bauch, Christina; Boonekamp, Jelle J.; Korsten, Peter; Mulder, Ellis; Verhulst, Simon
Abstract: Telomere length and telomere shortening predict survival in many organisms. This raises the question of the contribution of genetic and environmental effects to variation in these traits, which is still poorly known, particularly for telomere shortening. We used experimental (cross‐fostering) and statistical (quantitative genetic "animal models") means to disentangle and estimate genetic and environmental contributions to telomere length variation in pedigreed free‐living jackdaws ( Corvus monedula ). Telomere length was measured twice in nestlings, at ages 4 ( n  = 715) and 29 days ( n  = 474), using telomere restriction fragment (TRF) analysis, adapted to exclude interstitial telomeric sequences. Telomere length shortened significantly over the nestling period (10.4 ± 0.3 bp day –1 ) and was highly phenotypically ( r P  = 0.95 ± 0.01) and genetically ( rG  > 0.99 ± 0.01) correlated within individuals. Additive genetic effects explained a major part of telomere length variation among individuals, with its heritability estimated at h 2  = 0.74 on average. We note that TRF‐based studies reported higher heritabilities than qPCR‐based studies, and we discuss possible explanations. Parent–offspring regressions yielded similar heritability estimates for mothers and fathers when accounting for changes in paternal telomere length over life. Year effects explained a small but significant part of telomere length variation. Heritable variation for telomere shortening was low ( h 2  = 0.09 ± 0.11). The difference in heritability between telomere length (high) and telomere shortening (low) agrees with evolutionary theory, in that telomere shortening has stronger fitness consequences in this population. Despite the high heritability of telomere length, its evolvability, which scales the additive genetic variance by mean telomere length, was on average 0.48%. Hence, evolutionary change of telomere length due to selection is likely to be slow.